2022
DOI: 10.1111/jcpe.13628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of different techniques to seal the alveolus during alveolar ridge preservation: Meta‐regression and network meta‐analysis

Abstract: Aim: To evaluate the efficacy of different techniques to seal the alveolus (flap advancement [FA], open healing with barrier [OHB], and open healing without barrier [OHNB]) during alveolar ridge preservation (ARP) in terms of horizontal ridge width resorption. Materials and Methods: Randomized trials of at least 2 months duration comparing at least two techniques to seal the alveolus against each other or against spontaneous healing (SH) were eligible. Searches were conducted in MEDLINE via PubMed, EMBASE, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
2
12
0
Order By: Relevance
“…Moreover, the instability in the size of the alveolar fossa can compromise the accuracy of the installation of the removable denture or implant; the patient’s chewing function and facial image are affected during the healing time, and the quality of life is reduced. The alveolar process contracts to a certain extent due to the reduction of the biomechanical stimulation and the physiological remodeling of the alveolar bone to fill the postextraction space. Some studies showed that bone remodeling results in 40–60% of the vertical and horizontal bone loss during the first two years of alveolar bone healing. , Bio-Oss is widely used in clinical practice for the preservation of the alveolar ridge, achieving good results to some extent. However, it is prone to collapse, and it does not maintain a good and stable shape .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the instability in the size of the alveolar fossa can compromise the accuracy of the installation of the removable denture or implant; the patient’s chewing function and facial image are affected during the healing time, and the quality of life is reduced. The alveolar process contracts to a certain extent due to the reduction of the biomechanical stimulation and the physiological remodeling of the alveolar bone to fill the postextraction space. Some studies showed that bone remodeling results in 40–60% of the vertical and horizontal bone loss during the first two years of alveolar bone healing. , Bio-Oss is widely used in clinical practice for the preservation of the alveolar ridge, achieving good results to some extent. However, it is prone to collapse, and it does not maintain a good and stable shape .…”
Section: Introductionmentioning
confidence: 99%
“…Tooth extraction leads to dimensional changes in bone architecture and the mucosal tissue will also collapse immediately 1 . Moreover, compromised extraction sockets undergo more pronounced atrophy as a result of the natural remodeling process 2–4 . However, these soft and hard tissue changes in the required dental implant area are most likely to lead to increased difficulty in placing the implant in a suitable position for prosthodontics, especially, it might be a great challenge to achieve acceptable aesthetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Preservation of hard tissue with a prolonged healing time before implant placement has been suggested when buccal bone plate loss reaches more than 50% 1 . Bone substitute was commonly used to fill the extraction socket during ARP, such as artificial synthetic materials, xenograft, and autogenous or allogenic graft materials, and barrier membrane were used to cover the bone‐grafting materials 2 . For counteracting pressure and muscular activity from soft tissue, it is difficult to maintain contour stability when using absorbable membrane with particulate bone grafts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations